Structural, Gas Sensing and Dielectric Properties of HoXFe1-X FeO3 Perovskite Compound - Al- Aleem, Ali Abd; Al-Hilli, Muthafar F. (Iraqi Journal of Science, 2022)
Environmental pollutions and resources depletion motivates scientific research to innovate technologies for sustainable productive systems. To develop gas sensing substance with optimized performance a perovskite compound of HoxFe1-x FeO3 (where x= 0, 0.01, 0.03 and 0.05) were prepared by standard solid state reaction technique. The crystal structure was studied by XRD, which confirmed the formation of polycrystalline orthorhombic structure with space group Pbnm type perovskite. The preferred crystal growth of the main peak was (211). The structural parameters were also calculated and it was found that the lattice constants and particle size increased with the Ho doping ratio. The electrical properties were studied using the Hall effect, studied using the Hall effect, where the Hall coefficient, D.C conductivity (from 2.24E-06 (Ω-1.cm-1) at x=0) to 2.67E. -06 (Ω-1.cm-1) at x=0.05), mobility) 7.26 (cm2 / V.sec) at x=0 and decreased to 5.97 (cm2 / V .sec) at x=0.05 (and the concentration of charge carriers (2.14 E13 cm-3 at x=0 ) to 2.79E. 13 cm-3 at x=0.05 ) were calculated. The charge carrier concentration increased and charge mobility decreased with Ho addition. The Hall coefficient results revealed an n-type conduction mechanism. The dielectric constant ε r (in its real and imaginary parts) decreased with the increase in frequency of the applied electric field. tan δ and the AC conductivity were also calculated, and It was found that with the raise in the doping rate, the values of AC conductivity increase while tan δ decreases.